Management speak: Why we listen to what management gurus tell us - GREATBATCH, David (Institutional Knowledge at Singapore Management University, 2005)
Based on primary research into the public lectures of management gurus, this book analyzes how such gurus disseminate their ideas, values and visions on the international management lecture circuit. Adopting a novel conceptual/theoretical perspective, it brings together insights from the fields of management, sociology, media studies, communications and social psychology.